Uncertainty, Action, and Interaction: In Pursuit of Mixed-Initiative Computing - Horvitz, Eric (Intelligent Systems, 1999)
Recent debate has highlighted differing views on the most promising opportunities for userinterface innovation. 1 One group of investigators has expressed optimism about the potential for refining intelligent-interface agents, suggesting that research should focus on developing more powerful representations and inferential machinery for sensing a user’s activity and taking automated actions. 2–4 Other researchers have voiced concerns that efforts focused on automation might be better expended on tools and metaphors that enhance the abilities of users to directly manipulate and inspect objects and information. 5 Rather than advocating one approach over the other, a creative integration of direct manipulation and automated services could provide fundamentally new kinds of user experiences, characterized by deeper, more natural collaborations between users and computers. In particular, there are rich opportunities for interweaving direct control and automation to create mixed-initiative systems and interfaces.